From the bacterial citrus microbiome to the selection of potentially host-beneficial microbes - Penyalver, Ramón; Roesch, Luis F. W.; Piquer-Salcedo, Jaime E.; Forner-Giner, María A.; Alguacil, María M. (Elsevier, 2022)
Citrus is the most cultivated fruit crop worldwide. The modern citrus industry needs new bioproducts to overcome phytopathological threats, tolerate stresses and increase yield and quality. Mutualistic microbes from roots significantly impact host physiology and health and are a potentially beneficial resource. The bacterial microbiome can be surveyed to select potentially host-beneficial microbes. To achieve this goal, a prevalent “core-citrus” bacterial microbiome was obtained by picking those operational taxonomic units (OTUs) shared among samples within and across two Citrus rootstock genotypes grown in the same soil for more than 20 years. A sub-selection of main OTUs from the defined "core-citrus" microbiome was made based on abundance, host-enriched versus bulk soil, and rhizosphere-indicator species. In parallel, an extensive census of the cultivable microbiota was performed to collect a large number of bacterial citrus isolates. Metataxonomic data were linked to cultured microbes, matching 16S rRNA gene sequences from bacterial isolates with those counterpart OTU reference sequences from the selected bacterial "core-citrus" microbiome. This approach allowed selection of potentially host-beneficial bacteria to mine for agricultural probiotics in future biotechnological applications required for the citrus industry.